Herbal placebo response in clinical trials on irritable bowel syndrome: a systematic review and meta-analysis - Huang, Kaiyue; Lv, Mi; Zheng, Ting; Wang, Fengyun; Tang, Xudong; Lv, Lin (Frontiers in Pharmacology, 2024)
Aim of the study: To systematically evaluate the herbal placebo response in randomized controlled trials (RCTs) of herbal medicine on irritable bowel syndrome (IBS). Materials and methods: We searched for RCTs with herbal placebo groups for IBS in PubMed, EMBASE, the Cochrane Library, the China National Knowledge Infrastructure (CNKI), the Wan Fang database and Sinomed database from January 31, 1994 to November 2023, and the quality of the literature was evaluated by the Cochrane risk of bias assessment criteria. The primary outcome indicators were response rate, abdominal pain and stool improvement rate, which were analyzed by single-group rate meta-analysis. Secondary outcomes were analyzed in subgroups based on diagnostic criteria, duration of treatment, subtype, research locations, placebo form, and presence of herbal ingredients to look for factors affecting respond rate. RESULTS: The study included 24 papers, involving a total of 2596 patients. Of these, 1151 IBS patients were treated with the herbal placebo. The placebo response rate in IBS patients in the herbal placebo group was 37% (P < 0.01,I 2 = 75%). A total of 287 patients in five studies were given the herbal placebo, and the improvement rate of abdominal pain was 29% (P = 0.83, I 2 = 0%). Four studies enrolled a total of 212 patients with IBS who received herbal placebo, and the stool improvement rate was 46% (P = 0.02<0.05, I 2 = 71%). The research locations and treatment duration were sources of heterogeneity (P < 0.05). Conclusions: There is a significant herbal placebo response in patients with IBS. Different research locations and treatment durations are major sources of heterogeneity that may affect IBS patient response rates. The addition of a low dose of herbal ingredients when simulating an herbal placebo does not exaggerate the therapeutic effect of the placebo. There is a lack of uniformity and standardization in the preparation and evaluation of herbal placebos.